Performance and complexity comparison of service oriented architecture and microservices architecture. (19th May 2021) - Raj, Vinay; Sadam, Ravichandra
Microservices has emerged as a new architectural style of designing applications to overcome the challenges of service oriented architecture (SOA). With the evolution of microservices architecture, architects have started migrating legacy applications to microservices. However, some of the architects are in chaos whether to migrate the application from SOA to microservices or not. The need for empirical evaluation and comparison of both the SOA and microservices architecture is also on-demand. This work helps the software architects in better understanding of the technical differences between both styles. We, therefore, present a comparison of a web application that is designed using both SOA and microservices architectures. The comparison is presented with two different parameters: 1) complexity with architectural metrics; 2) performance with load testing. It is clear from the results that though the complexity of microservices architecture is high, the response time for processing the requests is very fast compared to SOA services.